Family Functioning: Perspectives of Adolescents - Erin Ratna Kustanti; Tina Afiatin; Arum Febriani (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The aim of the study was to explore family functioning, particularly the roles of fathers and mothers according to the perspective of adolescents. This qualitative study was conducted based on data obtained using open- ended questionnaire. The data were analyzed using descriptive analysis.The subject of the study consisted of 600 adolescents in Junior High School (41.8% of the population were boys and 58.2% of the population were girls) ranged from 12-16 years old. The results of the study show that adolescents gave positive responses to family functioning. In their perspectives, mothers’ role is higher (93.5%) compared to fathers’ role (84.49%). According to them, mothers were perceived to have higher role compared to fathers in every aspect. Fathers were perceived to have good role in the quality of role (93%), attitude in handling dangerous situations (91%) and the quality of relationship (88.83%), as well as attitude in handling dangerous situations and responding to problems. However, fathers were perceived as lack of openness and involvement in solving problems. This finding has implications for the need to increase and reinforce the role of fathers in accomplishing family functioning